Personal Branding Kerajinan Adat Papua “The Golden Sunset of Honai” Sebagai Pelestarian Budaya Nusantara - halim, Abdul; Rina Rachmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop the concept of personal branding in Papuan traditional crafts through a work entitled “The Golden Sunset of Honai” as an effort to preserve the cultural heritage of the Indonesian archipelago. The background of this research is based on the declining understanding of the younger generation toward Papuan culture as well as the lack of innovation in introducing traditional crafts to the wider community.This study employs a Research and Development (R&D) method consisting of four stages, namely defining, designing, developing, and disseminating. A descriptive quantitative approach was used to analyze respondents’ assessments of the developed product. Data were collected through a Likert scale questionnaire constructed based on four indicators. The data were analyzed using percentage techniques to determine the level of public acceptance of the developed concept.The results indicate that the concept of “The Golden Sunset of Honai” is rated very good, as it is able to visually, aesthetically, and emotionally represent the cultural values of Papua while remaining relevant to modern lifestyles. The implementation of culture-based personal branding has proven to be effective in increasing public interest, understanding, and appreciation of Papuan traditional crafts.This study provides practical contributions to the development of culture-based craft products as well as theoretical contributions to the study of personal branding in cultural preservation.